2020
DOI: 10.1016/j.dyepig.2019.108144
|View full text |Cite
|
Sign up to set email alerts
|

A colorimetric and ratiometric fluorescent probe with Meldrum's acid as the recognition group for in vitro and in vivo imaging of hypochlorite

Abstract: The detection of ClOis vital to comprehend the accurate effect of ClOin various diseases and therapeutic interventions by fluorescent probe method. Herein, a special ratiometric probe DDD was designed and efficiently synthesized via a simple process for hypochlorite detection. The selectivity and sensitivity of probe DDD was excellent and the detection was not influenced by other reactive oxygen species. Probe DDD exhibited a fast response (< 1 s), wide Stokes Shift (> 100 nm), sensitive limit of detection ( 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 48 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…The synthesis strategy could be concluded that the starting material 6-methoxytetralone was subsequently demethylated to obtain the free hydroxyl group, which underwent smile rearrangement to obtain the amino compound, followed by protection of the amino group with iodomethane, and after Vilsmeier-Haack reaction and condensation reaction the probe product ADT-MAM was finally obtained. With Meldrum's acid as the recognition group, another fluorescent probe based on tetralone scaffold for the detection of ClOwas also reported by the same group [125]. The probe DDD (Fig.…”
Section: Application Of Tetralone Moiety In Fluorescent Probesmentioning
confidence: 90%
“…The synthesis strategy could be concluded that the starting material 6-methoxytetralone was subsequently demethylated to obtain the free hydroxyl group, which underwent smile rearrangement to obtain the amino compound, followed by protection of the amino group with iodomethane, and after Vilsmeier-Haack reaction and condensation reaction the probe product ADT-MAM was finally obtained. With Meldrum's acid as the recognition group, another fluorescent probe based on tetralone scaffold for the detection of ClOwas also reported by the same group [125]. The probe DDD (Fig.…”
Section: Application Of Tetralone Moiety In Fluorescent Probesmentioning
confidence: 90%
“…[5][6][7] While, high concentrations of hypochlorite (ClO À ) have been linked to a variety of diseases, including atherosclerosis, nephropathy, neurodegenerative disorders and cancer. [8][9][10][11][12] At the same time, the elaborate interrelationships between ClO À concentration and various physiological processes are not well understood. Thus, real-time visual imaging monitoring of hypochlorite changes in living cells is very important.…”
Section: Introductionmentioning
confidence: 99%
“…It plays a role in the host innate immune response against invading bacteria and other pathogens, and is generated mainly by the peroxidation of chloride ion catalyzed by leukocyte myeloperoxidase (MPO) [5–7] . While, high concentrations of hypochlorite (ClO − ) have been linked to a variety of diseases, including atherosclerosis, nephropathy, neurodegenerative disorders and cancer [8–12] . At the same time, the elaborate interrelationships between ClO − concentration and various physiological processes are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Several conventional and recently developed methods for detecting hypochlorites such as colorimetric titration [5], colorimetry using organic solvents [6], electro-chemical analysis [7] and fluorescence [8] require a complicated preparation procedure so that a new detection method that is simple but rapid, selective and accurate is needed when dialing with the determination of hypochlorite in huge number of environmental samples.…”
Section: Introductionmentioning
confidence: 99%